The Military Orthopedics Tracking Injuries and Outcomes Network: A Solution for Improving Musculoskeletal Care in the Military Health System. Issue 3 (26th November 2020) - Mauntel, Timothy C; Tenan, Matthew S; Freedman, Brett A; Potter, Benjamin K; Provencher, Matthew T; Tokish, John M; Lee, Ian E; Rhon, Daniel I; Bailey, James R; Burns, Travis C; Cameron, Kenneth L; Grenier, Eric S; et al.
Abstract: Introduction: Musculoskeletal injuries are an endemic amongst U.S. Military Service Members and significantly strain the Department of Defense's Military Health System. The Military Health System aims to provide Service Members, military retirees, and their families the right care at the right time. The Military Orthopedics Tracking Injuries and Outcomes Network (MOTION) captures the data that can optimize musculoskeletal care within the Military Health System. This report provides MOTION structural framework and highlights how it can be used to optimize musculoskeletal care. Materials and Methods: MOTION established an internet-based data capture system, the MOTION Musculoskeletal Data Portal. All adult Military Health System patients who undergo orthopedic surgery are eligible for entry into the database. All data are collected as routine standard of care, with patients and orthopedic surgeons inputting validated global and condition-specific patient reported outcomes and operative case data, respectively. Patients have the option to consent to allow their standard of care data to be utilized within an institutional review board approved observational research study. MOTION data can be merged with other existing data systems (e.g., electronic medical record) to develop a comprehensive dataset of relevant information. In pursuit of enhancing musculoskeletal injury patient outcomes MOTION aims to: (1) identify factors which predict favorable outcomes; (2) develop models which inform the surgeon and military commanders if patients are behind, on, or ahead of schedule for their targeted return-to-duty/activity; and (3) develop predictive models to better inform patients and surgeons of the likelihood of a positive outcome for various treatment options to enhance patient counseling and expectation management. Results: This is a protocol article describing the intent and methodology for MOTION; thus, to date, there are no results to report. Conclusions: MOTION was established to capture the data that are necessary to improve military medical readiness and optimize medical resource utilization through the systematic evaluation of short- and long-term musculoskeletal injury patient outcomes. The systematic enhancement of musculoskeletal injury care through data analyses aligns with the National Defense Authorization Act (2017) and Defense Health Agency's Quadruple Aim, which emphasizes optimizing healthcare delivery and Service Member medical readiness. This transformative approach to musculoskeletal care can be applied across disciplines within the Military Health System.